Virtual screening and molecular dynamics simulation study of ATP-competitive inhibitors targeting mTOR protein - Jin, Mei-Yu; Yu, Hao; Deng, Qiong; Wang, Zhu; Wang, Jie-Yan; Li, Hao-Long; Liang, Hui (PloS one, 2025)
In order to explore efficient ATP-competitive mTOR inhibitors and aid the development of targeted anticancer drugs, this study focuses on virtual screening and molecular dynamics simulations. The compounds were sourced from the ChemDiv commercial compound library, and through virtual screening, 50 ligands with favorable binding modes and excellent docking scores were selected from 902,998 compounds. Molecular dynamics simulations, including RMSD (Root Mean Square Deviation) and RMSF (Root Mean Square Fluctuation), were used to further evaluate these 50 ligands. Structural stability, key residue interactions, hydrogen bonding, binding free energy, and other factors were quantitatively and qualitatively analyzed. Top1, top2, and top6, which exhibited outstanding performance, were identified. Simulations revealed that they bind stably in the active region of the mTOR protein, forming hydrogen bonds, π-π interactions, and hydrophobic interactions with key amino acid residues such as VAL-2240 and TRP-2239. This study provides a solid theoretical foundation for the development of mTOR inhibitors. Subsequent efforts will focus on optimizing these compounds, targeting structural adjustments to enhance their biological activity and specificity towards mTOR, thereby achieving more precise targeting and treatment of tumors.